A Pendampingan UMKM dalam Penerapan Teknologi Digital guna Meningkatkan Daya Saing Usaha: Pendampingan UMKM dalam Penerapan Teknologi Digital guna Meningkatkan Daya Saing Usaha - armiani, Armiani (Ikatan Cendekiawan Muda Akuntansi, 2023)
Digital technology can be a solution to help MSME players to increase their business competitiveness, with various benefits offered. Indonesia has also implemented the 2021-2024 digital roadmap and the national digital economy, which contains strategies to accelerate the realization of digital infrastructure, in order to encourage collaboration that fosters synergy among stakeholders. PKM program aims to assist MSME actors to provide education and practice using digital technology to increase sales and business competitiveness. PKM method with Participatory Action Research (PAR) approach, the participants are MSME actors who come from tobacco farmers. This activity is also fully supported by the government through the NTB Provincial Industry Office. Digital technology as a tool for MSMEs to sustain their business and increase competitiveness globally, with several benefits (marketing, operations, management), so that MSMEs can determine and choose the right business strategy in the use of digital technology, one of the digital technologies practiced, namely the use of social media for marketing, including; Creating WhatsApp Business, personal/business email, business face book, and Instagram, as well as google business, as well as MSMEs gain knowledge to analyze profit calculations and can predict business development.